2014
DOI: 10.1080/13691058.2014.888096
|View full text |Cite
|
Sign up to set email alerts
|

‘Young clean and safe?’ Young people's perceptions of risk from sexually transmitted infections in regional, rural and remote Australia

Abstract: This paper examines young people's perceived vulnerability to sexually transmitted infections (STIs) and their efforts to create a sense of personal safety within an environment in which risks may be high and where STIs are highly stigmatised. The paper reports on findings from research involving both Indigenous and non-Indigenous 16- to 25-year-olds from remote, rural and regional Australia, including communities in the Northern Territory, Western Australia and South Australia. The study used qualitative meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
2
40
0
1
Order By: Relevance
“…This was reflected in situations involving non-peer-aged male partner's sexual coercion; harassment from partners for money or substances; condom-use refusal; violence; and substance use. Senior et al (2014) reported young women in other remote areas as also having to negotiate the terms of their sexual relationships around gender-based beliefs and expectations. Although the concepts of homosexual, lesbian or bisexual relationships were known by participants, they stated they occurred only in urban centres associated with binge drinking.…”
Section: Behaviours Contributing To Riskmentioning
confidence: 96%
“…This was reflected in situations involving non-peer-aged male partner's sexual coercion; harassment from partners for money or substances; condom-use refusal; violence; and substance use. Senior et al (2014) reported young women in other remote areas as also having to negotiate the terms of their sexual relationships around gender-based beliefs and expectations. Although the concepts of homosexual, lesbian or bisexual relationships were known by participants, they stated they occurred only in urban centres associated with binge drinking.…”
Section: Behaviours Contributing To Riskmentioning
confidence: 96%
“…(Senior witnessed event Sept. 2013) Drawn from a sample of 88 Indigenous young people in five locations in urban and remote Northern Australia, this research utilised a combination of qualitative approaches to explore young people's ideas about sexual relationships and violence. Our previous research (Chenhall, Davison, Fitz, Pearse, & Senior, 2013;Senior & Chenhall, 2008;Senior, Helmer, & Chenhall, 2014) in both remote and urban settings alerted us to the normalisation of violence in young people's relationships. In this paper we explored how this acceptance of violence can manifest in the experience and management of everyday relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to art therapy, body mapping can be used for advocacy, providing treatment information and support and in participatory research (Solomon, 2002). Internationally, the empirical literature on body mapping has burgeoned in the fields of social science, health and education on topics including HIV/AIDS (MacGregor, 2008;Maina, Sutankayo, Chorney, & Caine, 2014), undocumented workers (Gastaldo, Magalhaes, Carrasco, & Davy, 2012), refugee youth (Davy, Magalhaes, Mandich, & Galheigo, 2014), sexual health (Ramsuran & Lurwengu, 2008;Senior, Helmer, Chenhall, & Burbank, 2014), child poverty (Mitchell, 2006), gendered violence (Sweet & Escalante, 2015) and occupational dance injury (Tarr & Thomas, 2011).…”
Section: Original Articlementioning
confidence: 99%